The Powdery Mildew Effector CSEP0027 Interacts With Barley Catalase to Regulate Host Immunity - Yuan, Hongbo; Jin, Cong; Pei, Hongcui; Zhao, Lifang; Li, Xue; Li, Jiali; Huang, Wanting; Fan, Renchun; Liu, Wende; Shen, Qian-Hua (Frontiers in Plant Science, 2021)
Powdery mildew is one of the most important fungal pathogen diseases. The genome of barley mildew fungus, Blumeria graminis f. sp. hordei (Bgh), encodes a large number of candidate secreted effector proteins (CSEPs). So far, the function and mechanism of most CSEPs remain largely unknown. Here, we identify a Bgh effector CSEP0027, a member of family 41, triggering cell death in Nicotiana benthamiana. CSEP0027 contains a functional signal peptide, verified by a yeast secretion assay. We show CSEP0027 promotes Bgh virulence in barley infection using transient gene expression and host induced gene silencing (HIGS). Barley catalase HvCAT1 is identified as a CSEP0027 interactor by yeast two-hybrid screening, and the interaction is verified in yeast, in vitro and in vivo. Coexpression of CSEP0027 and HvCAT1 in barley cells results in altered localization of HvCAT1 from the peroxisomes to the nucleus. BSMV-silencing and transiently-induced gene silencing (TIGS) assays reveal HvCAT1 is required for barley immunity against Bgh. We propose CSEP0027 interacts with barley HvCAT1 to regulate host immunity and likely ROS homeostasis to promote fungal virulence during barley infection.